2010
DOI: 10.3109/1354750x.2010.511266
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA level of Charcot–Leyden crystal protein/galectin-10 is a marker for CRTH2 activation in human whole bloodin vitro

Abstract: CRTH2 is one of the prostaglandin D₂ receptors and plays a proinflammatory role in allergic diseases. Gene expression markers in whole blood induced by CRTH2 activation have not previously been reported. Using microarray analyses of 54 675 genes, we revealed modest gene expression changes in human whole blood stimulated in vitro by a selective CRTH2 agonist, DK-PGD₂. Five genes were found to exhibit 1.5- to 2.6-fold changes in expression. The expression of Charcot-Leyden crystal protein/galectin-10 (CLC/Gal-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Among the genes showing ≥3-fold differences in expression between IgG4-RD patients and controls, we selected CLC because of its clinical association with type I hypersensitivity such as bronchial asthma [ 23 , 24 ]. Furthermore, CLC protein has been reported to be a marker of chemoattractant receptor homologous molecule expressed on T-helper type 2 cells (CRTH2), a prostaglandin D2 receptor [ 25 ], and CLC expression has been observed in the cytoplasm of CD4 + CD25 + Tregs, with little expression in CD4 + CD25 - T cells [ 26 ]. We found that the level of CLC mRNA was significantly lower in IgG4-RD patients than in controls ( Fig 1 ), despite the serum IgE concentrations being higher in IgG4-RD patients ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the genes showing ≥3-fold differences in expression between IgG4-RD patients and controls, we selected CLC because of its clinical association with type I hypersensitivity such as bronchial asthma [ 23 , 24 ]. Furthermore, CLC protein has been reported to be a marker of chemoattractant receptor homologous molecule expressed on T-helper type 2 cells (CRTH2), a prostaglandin D2 receptor [ 25 ], and CLC expression has been observed in the cytoplasm of CD4 + CD25 + Tregs, with little expression in CD4 + CD25 - T cells [ 26 ]. We found that the level of CLC mRNA was significantly lower in IgG4-RD patients than in controls ( Fig 1 ), despite the serum IgE concentrations being higher in IgG4-RD patients ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…19 Overexpression of CLC/Gal-10 mRNA was noted in the peripheral blood of patients with aspirin-induced asthma, and mRNA levels of CLC/Gal-10 were also shown to be a marker of CRTH2 activation. 20,21 Genetic variation in CLC/Gal-10 was found to be associated with allergic rhinitis, and patients with seasonal allergic rhinitis were found to have elevated levels of CLC/Gal-10 present in nasal lavage fluid during allergy season. 22,23 Analysis of protein expression patterns in gut biopsy samples from patients with celiac disease found a positive correlation between CLC/Gal-10 levels and tissue damage, and a recent study showed that higher levels of CLC/Gal-10 mRNA distinguished children with eosinophilic esophagitis from control children.…”
mentioning
confidence: 99%
“…This gene is expressed in a variety of tissues and body fluids and is a known marker for allergic inflammation in asthma and allergic rhinitis. However, the role and function of CLC is not entirely understood[37].…”
mentioning
confidence: 99%